Impact on plant productivity under low-fertility sandy soil in arid environment by revitalization of lentil roots - Abd El-hady, Mohamed A.; Abd-Elkrem, Yasser M.; Rady, Mohamed O. A.; Mansour, Elsayed; El-Tarabily, Khaled A.; AbuQamar, Synan F.; El-temsah, Mohamed E. (Frontiers in Plant Science, 2022)
Lentil is one of the essential legume crops, which provides protein for humans and animals. This legume can improve soil fertility through nitrogen fixation which is imperative in low fertility soils. Growth and productivity of lentil could be enhanced through improving nutrition and root revitaliza-tion. Therefore, the objective of this study was to assess the impact of root activator (RA) and phos-phorus (P) application on morphological, physiological, agronomic and quality traits of lentil under newly reclaimed low fertility sandy soil in an arid environment. The RA was applied at four levels of 0 (RA0-untreated control), 1.25 (RA1), 2.5 (RA2), and 3.75 (RA3) l ha-1. RA contained 9% potassium humate, 1600 ppm indole butyric acid, 200 ppm gibberellic acid and 200 ppm naphthalene acetic acid. The recommended rate of phosphorus (P) fertilization in the newly reclaimed low fertility sandy soil (75 kg P2O5 ha-1) was applied and its amount was increased and decreased by 25 kg P2O5 ha-1 versus non-added control. Thus, P rates were applied at four rates 0 (P0; control), 50 (P1), 75 (P2) and 100 (P3) kg phosphorus pentoxide (P2O5) ha-1. Our results revealed that treated lentil plants with the high levels of both treatments (RA3 and P3) exhibited superiority of root measurements (root length, total number of nodules per plant, number of active nodules per plant, dry weights of active nodules and total root), and nitrogenase activity, chlorophyll a and b, carotenoids, yield traits, and seed proteins and carbohydrates. However, the recommended P level (75 kg P2O5 ha-1, P2) under the high level of RA (3.75 l ha-1, RA3) displayed non-significant differences in yield traits (plant height, 1000-seed weight, seed yield ha-1) and quality traits (protein and carbohydrate) with the high P level (100 kg P2O5 ha-1, P3). Accordingly, its recommended economically and environmentally to use this coapplication of RA3 and P3 in low fertility soil for better lentil growth, and seed yield and quality.